B316 Opioid-free anaesthesia and postoperative analgesia clinical pathway for enhanced recovery after pancreatoduodenectomy: a case series. (11th August 2022) - Liotiri, D; Sioka, E; Diamantis, A; Grapsidi, V; Stamatiou, G; Zacharoulis, D
Abstract : Background and Aims: Recently, there has been an increasing interest in the potential role of anaesthetic technique in reducing perioperative comlications and cancer recurrence. 1 There is emerging evidence that volatile anaesthetics and opioids may promote tumour cell survival and angiogenesis, whilst propofol seems to suppress tumour cell growth. 2, 3 Besides, opioid side effects such as nausea and vomiting, delayed gastric emptying (DGE), postopearative ileus, respiratory depression and sedation may add to postoperative complications and impede recovery. 4 Based on the available evidence and ERAS society recommendations 5 we developed a clinical pathway for Enhanced Recovery Anaesthesia and Analgesia for pancreatic surgery. Methods: The enhanced recovery anaesthesia and analgesia protocol we developed is shown in Figure 1 . With patient consent, we tested this protocol in four consecutive cases. Patients, perioperative characteristics and outcomes are shown in Table 1 . Anaesthesia technique was opioid-free & multimodal TIVA anaesthesia. All patients were extubated at the end of surgery and spent one night in the High Dependency Unit. They were discharged to the ward the following morning. Results: None of the patients received parenteral or oral opioids either intraoperatevely or postoperatively. All patients remained pain-free during their hospital stay and achieved ERAS outcomes early. Three patients developed DGE. Otherwise the patients had an uncomplicated recovery. Conclusions: Our protocol achieved an opioid-free experience, with the advantage of avoiding opioid side effects which may interfere with early surgical outcomes especially after pancreatic surgery. Future studies on models of enhanced recovery anaesthesia and analgesia and their effect on surgical and oncological outcomes are therefore recommended.